Epilepsy in companion animals: A theoretical reference - Mori Santalucia Monteiro, Carolina; Gomes, Lucas Alécio (Pubvet, 2024)
This work is a theoretical framework aimed at analyzing the most recent scientific publications on epilepsy in companion animals in order to consider current and classic aspects of the disease, mainly in the clinical, diagnostic and therapeutic aspects, as well as proposed terminology and forms of classification of the different presentations of the disease. The method chosen for this was the analysis of publications dated between 2015 and 2021 with the keywords “epilepsy cats and dogs”, “epilepsy cats”, “seizure cats”, “seizure cat dog” and “international veterinary epilepsy task force” on the PubMed online platform, and subsequent analysis of the results obtained to prepare the theoretical framework. Previously published publications were also considered when cited by the authors of the main literature of this paper, when considered relevant to the present discussion. Finally, the technical-scientific evolution in the field of Veterinary Medicine is considered when seeking to establish specific procedures for dogs and cats, as well as for the different presentations of the disease, although there remains some lack of greater precision of data and specific protocols for each species and presentation of epilepsy.
Keywords: Dogs; cats; epilepsy; seizures